The use of probiotics in nutrition and herd health management in large Hungarian dairy cattle farms - Várhidi, Zsóka; Máté, Marietta; Ózsvári, László (Frontiers in Veterinary Science, 2022)
In the European Union, there is an increasing need for farm animal nutrition products whose positive effects can replace antibiotics that have been heavily used for decades. Thus, the use of probiotics started to increase in the past few years. In this study, a survey on the practical use of probiotics in Hungarian dairy cattle farms and the related experience of farm nutrition experts was conducted. In addition, we surveyed the state of Hungary for probiotics production and distribution. After direct request via phone, nutrition experts responsible for farm feeding programs in 23 large commercial dairy cattle farms and eight managers in different feed distributor companies in Hungary filled out the relevant online questionnaires in 2018. The results show that 69.6% of the surveyed farms used probiotics, most often aiming at the optimization of rumen fermentation, protection against stressors, and supplementation of medical treatments. The most common expected beneficial effects of probiotics were more effective calf raising, larger milk yield, more stable rumen fermentation, and improved stress resistance. None of the respondents experienced any negative effects. In Hungary, five out of eight surveyed feed companies produced probiotic products for cattle, and one just distributed them. Company managers generally thought that farm nutrition experts did not have up-to-date knowledge on probiotics, which is why, these products are often not used in an effective way, and the experts' knowledge should be increased. The own experiments of the distributor companies showed that the probiotic products can improve feed digestibility, the efficacy of calf raising, and the reproductive performance of cows. According to the expectations of distributors, the next generation of probiotic products will be microencapsulated and will contain multiple strains and species of bacteria and prebiotics, too. The goal of the product development is to create probiotics with better effectiveness at a reasonable price, having a complex impact and easier application on the herd level. The study showed that probiotics are already frequently used to prevent diseases in Hungarian dairy herds. However, it can be concluded that there is room for improvement, especially concerning the knowledge transfer about the most effective use of probiotic products.